Coping with crisis: Livelihood vulnerabilities and food insecurity in Sudan’s current conflict - Kirui, Oliver K.; Rakhy, Tarig Alhaj; Siddig, Khalid; Taffesse, Alemayehu Seyoum; Abushama, Hala (International Food Policy Research Institute, 2025)
Sudan’s conflict, reignited in April 2023, represents not just a military contest between the Sudanese Armed Forces (SAF) and the Rapid Support Forces (RSF), but a total systemic collapse that has engulfed governance, infrastructure, markets, and public services. This conflict did not arise in a vacuum. Sudan has long faced structural vulnerabilities including weak institutions, a fragile economy, and climate-related stressors such as erratic rainfall and land degradation. The war, however, accelerated these pre-existing fault lines into a full-blown crisis.